Arcydziała literatury hiszpańskiej. Dziesięć wykladów - Redakcja (Wydawnictwo Naukowe UAM, 2016)
New interpretations of the finest literary works in Spanish culture by   eminent specialists in the field of Iberian Studies. In these 10 essays Polish  and Spanish literary theorists present their own original interpretations  of works in Spanish, and in doing so create a panorama spanning the  period from the Middle Ages to the second half of the 20th century. The  works discussed include: Juan Ruiz's The Book of Good Love, Fernando de  Rojas' La Celestina, The Life of Lazarillo de Tormes and of His Fortunes  and  Adversities  (anonymous),  Miguel  Cervantes'  Don  Quixote,  Pedro  Calderón de la Barca's Life is a Dream and The Constant Prince, The Regent's Wife by Leopoldo Alas (“Clarin”), Mist by Miguel de Unamuno,  Ramón del Valle‐Inclán's Bohemian Lights, Federico García Lorca’s The  House of Bernarda Alba and Eduardo Mendoza's The Truth about the  Savolta Case. In addition to describing these works' significance for Spanish literature, the authors of these analyses indicate how they function in  the international arena, as well as in Polish translation and reception  contexts.

Zbiór autorskich interpretacji wybranych arcydzieł literatury hiszpańskiej (od Księgi Dobrej Miłości Juana Ruiza z XIV w. przez Don Kichota Miguela Cervantesa z wieku XVII po Prawdę o sprawie Savolty Eduado Mendozy z XXw.) pióra wybitnych znawców literatury hiszpańskiej z Polski i Hiszpanii.
Masterpieces of Spanish Literature. Ten lectures
Keywords: Juan Ruiz; Fernando de Rojas; Łazik z Tormesu; Miguel de Cervantes; Miguel de Unamuno; Federico Garcia Lorca